Potential of iPSC-Derived Mesenchymal Stromal Cells for Treating Periodontal Disease. (14th March 2018) - Hynes, K.; Bright, R.; Marino, V.; Ng, J.; Verma, P. J.; Gronthos, S.; Bartold, P. M.
Abstract : Mesenchymal stromal cell-like populations have been derived from mouse-induced pluripotent stem cells (miPSC-MSC) with the capability for tissue regeneration. In this study, murine iPSC underwent differentiation towards an MSC-like immunophenotype. Stable miPSC-MSC cultures expressed the MSC-associated markers, CD73, CD105, and Sca-1, but lacked expression of the pluripotency marker, SSEA1, and hematopoietic markers, CD34 and CD45. Functionally, miPSC-MSC exhibited the potential for trilineage differentiation into osteoblasts, adipocytes, and chondrocytes and the capacity to suppress the proliferation of mitogen-activated splenocytes. The efficacy of miPSC-MSC was assessed in an acute inflammation model following systemic or local delivery into mice with subcutaneous implants containing heat-inactivated P . gingivalis . Histological analysis revealed less inflammatory cellular infiltrate within the sponges in mice treated with miPSC-MSC cells delivered locally rather than systemically. Assessment of proinflammatory cytokines in mouse spleens found that CXCL1 transcripts and protein were reduced in mice treated with miPSC-MSC. In a periodontitis model, mice subjected to oral inoculation with P . gingivalis revealed less bone tissue destruction and inflammation within the jaws when treated with miPSC-MSC compared to PBS alone. Our results demonstrated that miPSC-MSC derived from iPSC have the capacity to control acute and chronic inflammatory responses associated with the destruction of periodontal tissue. Therefore, miPSC-MSC present a promising novel source of stromal cells which could be used in the treatment of periodontal disease and other inflammatory systemic diseases such as rheumatoid arthritis.